Multiple Thromboses in a Patient with Systemic Lupus Erythematosus after Splenectomy - Deng-Ho Yang (Case Reports in Immunology)
Antiphospholipid syndrome is a disorder presenting with arterial or venous thrombus and a history of fetal loss. Early diagnosis and adequate treatment is important to prevent multiple organ failures. Here, we described a woman with a two-year history of systemic lupus erythematosus with severe nephrotic syndrome, manifested multiple thrombi over the portal vein and the inferior vena cava, combined with acute renal infarction. The patient underwent splenectomy 10 months ago. Initially, she received anticoagulant treatment and low-dose glucocorticoid, but multiple organ failure progressed. After emergency plasma exchange followed by glucocorticoid pulse therapy, the patient recovered.